Developing Students’ Speaking Performance through Mastering Question Words in Islamic University Setting - Ana Kuliahana; Abdul Gafur Marzuki; Andi Nurfaizah (University of Muhammadiyah Malang, 2025)
This study aims to identify students’ speaking performance at English Department students of State Islamic University of Datokarama Palu could be developed through mastering question words method. It was designed as a collaborative classroom action research and divided into two cycles. Data came from class observation, field notes, questionnaire, and speaking test over six meetings of speaking lesson. The research included 22 students. The researchers identified the students’ speaking performance based on the criteria of success established. The findings showed that the use of questions in the teaching and learning process helps to increase students' motivation, responsiveness, and enthusiasm, as well as, of course, their courage to speak English. This method can also be used to encourage students to understand the question's content before they respond to it and to offer them the chance to verbally express their ideas. Only five students who received a score of at least were detected in the first cycle's assessment of students' speaking performance. It meant that only 23% of the students met the success criteria. The students' achievement was then discovered in the second cycle by seventeen students or 77%. It suggests that the success requirements have been met or that the question words technique can improve students' speaking performance.